Numerical study on scale effect of nominal wake of single screw ship. (1st August 2015) - Wang, Zhan-Zhi; Xiong, Ying; Wang, Rui; Shen, Xing-Rong; Zhong, Chen-Hua
Abstract: A 4000TEU container ship was studied without considering free surface effect, and the viscous flow fields of ship at different scales were solved numerically by RANS method, numerical uncertainty analysis was employed according to factors of safety method for Richardson extrapolation, scale effect of axial nominal wake field was analyzed in details. It shows that the reciprocal of mean axial wake fraction of propeller disc exhibits a near linear dependence on Reynolds number in logarithmic scale. For the single screw ship without bilge vortex, linear function is fit perfectly for the relationship between the reciprocal of mean axial wake fraction at each radius, reciprocal of amplitude of wake peak right above propeller disc and Reynolds number in logarithmic scales. In inner area of propeller disc, the reciprocal of amplitude of wake valley and wake peak right down propeller disc reveal nearly linear dependence on Reynolds number in logarithmic scales. While in outer area, the amplitude of wake peak and valley decline rapidly to potential wake fraction, and the wake width reveals negative exponent power function dependence on Reynolds number in logarithmic scales. On this basis, an extrapolated wake field scaling method is proposed. Highlights: Viscous flow fields of ships at different scales were solved numerically. Scale effect of axial nominal wake field was analyzed in details. An extrapolated wake field scaling method of nominal wake field was proposed.